"Slow" skeletal muscles across vertebrate species. Issue 1 (December 2015) - Luna, Victor; Daikoku, Eriko; Ono, Fumihito
Abstract Skeletal muscle fibers are generally classified into two groups: slow (type I) and fast (type II). Fibers in each group are uniquely designed for specific locomotory needs based on their intrinsic cellular properties and the types of motor neurons that innervate them. In this review, we will focus on the current concept of slow muscle fibers which, unlike the originally proposed version based purely on amphibian muscles, varies widely depending on the animal model system studied. We will discuss recent findings from zebrafish neuromuscular junction synapses that may provide the framework for establishing a more unified view of slow muscles across mammalian and non-mammalian species.